2016
DOI: 10.1186/s12889-016-3163-1
|View full text |Cite
|
Sign up to set email alerts
|

Gendered sexual uses of alcohol and associated risks: a qualitative study of Nigerian University students

Abstract: BackgroundAlcohol misuse among young people is a global phenomenon. In many countries, young people engage in heavy drinking and this exacerbates risky sexual behaviour. In Nigeria, alcohol held multiple roles in the traditional era but was mainly consumed by adult males for pleasure. Adult females and young people were culturally constrained from drinking in most communities. In contemporary Nigeria, young people’s drinking is increasing, and many engage in sexual intercourse under the influence of alcohol.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Also, psychoactive substance users may engage in multiple sexual partnerships expecting better sexual experiences (expectancies) with different partners. Similarly, Doku [7] and [58] reported that young people in Ghana and Nigeria respectively often used psychoactive substances to enhance their sexual pleasures.…”
Section: Plos Onementioning
confidence: 99%
“…Also, psychoactive substance users may engage in multiple sexual partnerships expecting better sexual experiences (expectancies) with different partners. Similarly, Doku [7] and [58] reported that young people in Ghana and Nigeria respectively often used psychoactive substances to enhance their sexual pleasures.…”
Section: Plos Onementioning
confidence: 99%
“…Users of psychoactive substances often have the perception that they will provide them with benefits that no other substance can. According to the expectancy theory, users suppose that psychoactive substances will reduce sexual inhibition, such as lack of confidence to approach sexual partners, and on the other hand, enhance benefits such as sexual pleasure, arousal, and performance (7)(8)(9)(10). Such expectancies often drive the desire to engage in high-risk sexual behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that users of psychoactive substances perceive them to be associated with increasing sexual arousal, delaying premature ejaculation, and prolonging sexual intercourse (8). Such perceptions are often driven by cultural beliefs that portray good sex to be long and penetrative (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations